Pengaruh Kepemimpinan Kepala Sekolah Dan Iklim Kerja Terhadap Kinerja Guru SMA Di Kecamatan Samarinda Utara - Haryanto, Puji; Subagyo, Lambang; Dwiyono, Yudo (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
This study aims to determine the effect of (1) Principal leadership on teacher performance, (2) the work climate on teacher performance, (3) work climate and principals' leadership together on teacher performance. The research method used is the method of correlation. The research respondents were high school teachers in SMA Negeri 9 Samarinda , SMA Negeri 12 Samarinda , SMA Negeri 13 Samarinda , and SMA Islam Bunga Bangsa Samarinda in North Samarinda Sub-District as many as 106 people . The technique of collecting data uses a structured questionnaire, with three instruments, namely the work climate, principal leadership and teacher performance. The results of the study show (1) there is a positive effect of principals' leadership on teacher performance with a correlation coefficient = 0.078, (2) there is a positive effect of the work climate on teacher performance with a correlation coefficient = 0.206; (3) there is a positive effect of work climate and principal leadership on teacher performance with a correlation coefficient = 0.302 Keywords: work climate, leadership and performance